BENTUK LAYANAN PENDIDIKAN BAGI ANAK INKLUSI - Desy Widya Sapitri; Rabiatul Adawiah; Yunica Rike Ulfa; Opi Andriani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The government's high level of attention to the implementation of education in Indonesia is proven by the enactment of Law No. 20 of 2003 concerning the National Education system, namely equal distribution of education without discrimination against Children with Special Needs (ABK). However, the implementation of inclusive education in Indonesia has not gone perfectly according to the goals of implementing inclusive education. Several schools appointed as implementers of inclusive schools are only operating at a modest level. Even though there are a lot of inclusive schools in Indonesia in quantity, the quality of inclusive schools in Indonesia is still lacking. This research aims to explain the form of educational services for inclusive children using the literature study method used, namely theoretical studies whose information can be obtained through books, websites, journals and scientific works and from other sources. The forms of educational services for children with special needs are divided into 3, namely Segregated Service Forms; Form of Integration/Integrated Services; Forms of Inclusive Education Services. Parental involvement in children's education is a driving and determining factor in the development of inclusive education throughout the world.